Seroprevalence of Canine Toxocariasis in Three Rural Areas of Fars Province, Southern Iran - Ali Pouryousef; Seyyed Mohammad Hashemi; Mostafa Omidian; Fattaneh Mikaeili; Bahador Sarkari (Iranian Journal of Parasitology, 2024)
Background: Toxocara canis is one of the most important causes of animal toxocariasis with global distribution. We aimed to find out the seroprevalence of toxocariasis in dogs in a rural area in Fars Province, south of Iran.